Analisis Celah Keamanan Jaringan WPA dan WPA2 dengan Menggunakan Metode Penetration Testing - Okario, Albert; Hendra Suputra, I Putu Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
With the rapid development of communication and information technology, wireless local area network (WLAN) security has become crucial and a major concern, as data traffic is transmitted without the need for cables. Internet-connected network devices are inherently insecure and can be exploited by crackers or hackers. When data communicates or connects in the data traffic, where data is sent and passes through a series of terminals to reach its destination, an irresponsible user has the opportunity to modify or intercept the data. Therefore, designing a WLAN network connected to the internet must be carefully planned to minimize undesirable incidents. The weakness of the IEEE 802.11 network that uses WEP encryption tends to make the encryption code more easily discoverable by hackers. Based on the aforementioned background, we conducted this research to identify vulnerabilities or security flaws in WPA and WPA2-PSK  networks using penetration testing methods.